Turning goals into results : - Collins, James (Harvard Business Review Press, 2017)
Most executives have a big, hairy, audacious goal. They write vision statements, formalize procedures, and develop complicated incentive programs--all in pursuit of that goal. In other words, with the best of intentions, they install layers of stultifying bureaucracy. But it doesn't have to be that way. In this book, Jim Collins introduces the catalytic mechanism, a simple yet powerful managerial tool that helps translate lofty aspirations into concrete reality. Catalytic mechanisms, the crucial link between objectives and performance, are a galvanizing, nonbureaucractic means to turn one into the other. What's the difference between catalytic mechanisms and most traditional managerial controls? Catalytic mechanisms share five characteristics: (1) they produce desired results in unpredictable ways; (2) they distribute power for the benefit of the overall system, often to the discomfort of those who traditionally hold power; (3) catalytic mechanisms have teeth; (4) they eject "viruses"--those people who don't share the company's core values; and (5) they produce an ongoing effect. To illustrate how catalytic mechanisms work, the author draws on examples of individuals and organizations that have relied on such mechanisms to achieve their goals. The same catalytic mechanism that works in one organization, however, won't necessarily work in another.